Different Dynamic Distribution in Chickens and Ducks of the Hypervirulent, Novel Genotype Fowl Adenovirus Serotype 4 Recently Emerged in China - Pan, Qing; Yang, Yanchao; Shi, Zhibin; Liu, Linlin; Gao, Yulong; Qi, Xiaole; Liu, Changjun; Zhang, Yanping; Cui, Hongyu; Wang, Xiaomei (Frontiers in Microbiology, 2017)
A hypervirulent fowl adenovirus serotype 4 (FAdV-4) has caused hepatitis-hydropericardium syndrome (HHS) with mortalities that range from 30% to 80% in outbreaks across China since 2015. The FAdV-4 strain was characterized as a novel genotype based on the specific genome characteristics. However, our understanding of the dynamic distribution, tissue tropism, and pathogenesis of the novel FAdV-4 is incomplete. In this study, a new, sensitive and FAdV-4-specific real-time PCR was developed and applied to detect the dynamic distribution of the duck origin, novel FAdV-4 strain HLJDAd15 in experimentally infected special-pathogen free (SPF) chickens and ducks. Notably, the pathogenicity and replication pattern of HLJDAd15 were completely different between chickens and ducks. Severe hydropericardium and 10% mortality were induced in chickens, whereas no clinical signs were observed in any duck. The virus replicated was detected throughout the study in both chickens and ducks. However, only one replication peak with a high virus concentration appeared in chickens at 5 days post infection (dpi), whereas two peaks with relatively low virus titres appeared in ducks at 7 and 21 dpi. Thus, ducks could be a natural reservoir of the novel FAdV-4 absent of clinical signs, and a new transmission route from ducks shedding FAdV-4 continually to chickens was revealed, which might aggravate the outbreak of HHS in chickens. This study provides the first accurate quantitative data for the replication kinetics of the novel FAdV-4 in different hosts. The different pathogenicity, dynamic distribution and replication pattern in chickens and ducks provide a foundation for further clarification of the pathogenesis of the novel FAdV-4.